How different believers’ perceptions of choosing halal hotels an empirical analysis of non-muslim customers in Jakarta - Ulfa, Nadiya; Arsyianti, Laily Dwi; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (Goodwood Publishing, 2022)
Purpose: The primary objective of this study was to understand the factors that influence non-Muslim clients' perceptions of halal hotels in DKI Jakarta, Indonesia. Research Methodology: Data were collected using questionnaires from 95 hotel guests in the DKI Jakarta region. Descriptive analysis and logistic regression were employed as analytical methods. Results: The results of the logistic regression revealed that education level and cost of hotel stay are significant determinants of non-Muslim consumers' selection of halal hotels. Limitations: This study was limited by its sample size of 95 visitors and geographical restrictions on the DKI Jakarta area. These variables may have affected the generalizability of our results. Contributions: This research enriches the halal tourism domain by elucidating non-Muslim guests' views on halal hotels and offering invaluable guidance for hoteliers, tourism entities, and policymakers to expand their target clientele in halal travel. Novelty: The novelty of this study lies in its focus on non-Muslim consumer perceptions, providing empirical evidence on how education and price influence hotel selection in the context of halal tourism.